Bifunctional interfacial engineering for piezo-phototronic enhanced photovoltaic performance of wearable perovskite solar cells. (August 2021) - Fahim, Muhammad; Firdous, Irum; Zhang, Weihai; Daoud, Walid A.
Abstract: The piezo-phototronic effect can effectively modulate the energy band structure at the interface of p-n or metal-semiconductor junction, manipulating the separation, transport, and recombination of photoinduced charges. While zinc oxide (ZnO) is a good electron transporting layer (ETL), its Lewis's basic nature and presence of surface defects lead to deprotonation of perovskite, resulting in severe degradation of perovskite solar cells (PSC). Herein, the ZnO surface is converted to ZnS, which acts as a bifunctional interfacial layer, passivating the ZnO/perovskite interface by reducing the hydroxyl (‒OH) group on the ZnO surface for improved stability and forming strong coordination with Pb 2+ of perovskite (Zn-S-Pb pathway) and thus adjusting the energy level for efficient electron transport. Consequently, the power conversion efficiency (PCE) of the flexible PSC is remarkably improved from 12.94% to 14.68% under static external strain of 1.5%, ascribed to the strain-induced piezo-polarization charges, which modulate the energy band structure of ZnS/ZnO and ZnS/perovskite interfaces. As a result, spatial separation of photoinduced carriers is facilitated, reducing recombination probability. The energy band diagram is proposed to elucidate the mechanism. This strategy enables effective utilization of the piezo-phototronic effect while enhancing device stability. Graphical Abstract: Power conversion efficiency and current density of flexible perovskite solar cell are enhanced from 12.94% and 21.82 mA cm −2 to 14.68% and 24.40 mA cm −2, respectively, via a tensile strain of 1.5% due to the piezo-phototronic effect modulating the band structure at ZnO/ZnS and ZnS/perovskite interfaces. ga1 Highlights: A bifunctional interlayer at ZnO/perovskite interface is introduced for enhancing device stability. Wearable PSCs with enhanced PCE is developed via the piezo-phototronic effect. A 14% enhancement in PCE reaching 14.68% with 1.5% tensile strain is achieved. PCE remains stable (90%) at 25 °C for 50 days and (84.2%) at 80 °C for 30 days. A piezo-phototronic modulated energy band alignment mechanism for core-shell ETL is proposed.